Alcohol and Road Traffic Injuries in Latin America and the Caribbean: A Case‐Crossover Study. (13th September 2017) - Borges, Guilherme; Monteiro, Maristela; Cherpitel, Cheryl J.; Orozco, Ricardo; Ye, Yu; Poznyak, Vladimir; Peden, Margie; Pechansky, Flavio; Cremonte, Mariana; Reid, Sandra D.; Mendez, Jesus
Abstract : Background: This study reports dose–response estimates for the odds ratio (OR) and population attributable risk of acute alcohol use and road traffic injury (RTI). Methods: Data were analyzed on 1, 119 RTI patients arriving at 16 emergency departments (EDs) in Argentina, Brazil, Costa Rica, Dominican Republic, Guatemala, Guyana, Mexico, Nicaragua, Panama, and Trinidad and Tobago. Case‐crossover analysis, pair‐matching the number of standard drinks consumed within the 6 hours prior to the RTI with 2 control periods (prior d/wk), was performed using fractional polynomial analysis for dose–response. Results: About 1 in 6 RTI patients in EDs were positive for self‐reported alcohol 6 hours prior to the injury (country range 8.6 to 24.1%). The likelihood of an RTI with any drinking prior (compared to not drinking) was 5 times higher (country range OR 2.50 to 15.00) and the more a person drinks the higher the risk. Every drink (12.8 g alcohol) increased the risk of an RTI by 13%, even 1 to 2 drinks were associated with a sizable increase in risk of an RTI and a dose–response was found. Differences in ORs for drivers (OR = 3.51; 95% CI = 2.25 to 5.45), passengers (OR = 8.12; 95% CI = 4.22 to 15.61), and pedestrians (OR = 6.30; 95% CI = 3.14 to 12.64) and attributable fractions were noted. Acute use of alcohol was attributable to 14% of all RTIs, varying from 7% for females to 19% for being injured as a passenger. Conclusions: The finding that the presence of alcohol increases risk among drivers and nondrivers alike may further help to urge interventions targeting passengers and pedestrians. Routine screening and brief interventions in all health services could also have a beneficial impact in decreasing rates of RTIs. Higher priority should be given to alcohol as a risk factor for RTIs, particularly in Latin America and the Caribbean. Abstract : Data on the prevalence and risk associated with drinking and driving are scarce or plainly unavailable for most countries in the Americas region. We performed a case‐crossover study among 1, 119 patients that suffered a road traffic injury at 16 emergency departments in Argentina, Brazil, Costa Rica, Dominican Republic, Guatemala, Guyana, Mexico, Nicaragua, Panama and Trinidad & Tobago. Differences in Odds Ratios (OR) for drivers (OR = 3.51; 95% CI = 2.25–5.45), passengers (OR = 8.12; 95% CI = 4.22–15.61) and pedestrians (OR = 6.30; 95% CI = 3.14–12.64), risk curves and attributable fractions were reported. Odds ratios of road traffic injury by alcohol volume consumed before injury, by type. X axis trimmed to 30 drinks.